REGENERASI KATION DAN ANION UNTUK PENURUNAN MINERAL AIR UMPAN BOILER DI UNIT PENGOLAHAN AIR PT BAKRIE SUMATERA PLANTATIONS, Tbk PALM OIL MILL KISARAN - Kurniawan, Muhammad; Effendi, Zulham; Purjianto, Purjianto (Jurnal Agro Fabrica, 2023)
Water is a crucial factor in ensuring smooth and high-quality production in palm oil mills. Minerals present in water can lead to scale formation, sedimentation, and equipment corrosion. Therefore, the demineralization process with cation and anion regeneration is beneficial to maintain water quality in accordance with op- erational standards. Water plays a vital role in the industrial sector; boilers, as primary steam generators, transform water into vapor through heating. However, operating without good water quality can result in issues like scale formation and corrosion. In water treatment processes, chemical substances are required for purification, such as Nalco 3276 for flocculation and Nalco 8173 for flocculant retention. The mineral content in water also affects chemical reactions, such as causing scale formation in boilers and influencing reaction processes. Demineral- ization is frequently employed across various industrial sectors, including palm oil mills, to treat boiler feedwater and other raw materials. Maintaining stable boiler feedwater usage by controlling pH and total hardness prevents problems in pipelines. This research focuses on cation and anion regeneration to reduce min- eral content in boiler feedwater at PT. Bakrie Sumatera Plantations, Tbk Palm Oil Mill Kisaran, with the aim to analyze the regeneration process using H2SO4 and NaOH dosages and identify factors causing issues during regeneration.